La fiducie, l'usufruit et la substitution : analyse de certaines incidences fiscales - Setlakwe, Paul (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
This article deals with income tax and succession duty implications resulting from the use of Quebec civil law trusts, usufructs and substitutions. In the first part, the author examines income tax consequences under the Income Tax Act (Canada) and the Taxation Act (Quebec). In the second part, the author examines the specific and unique rules provided in the Succession Duty Act (Quebec) with respect to each institution and various estate planning techniques which have been used